Problems restore the situation that existed before the infringement of intellectual property rights - Dyachenko, Serhii; Lihtanska, Diana (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The article examines the jurisprudence of various kinds of violations of human subjects of intellectual property arising in restoring the situation that existed before the violation of rights under the Civil Code of Ukraine, and studied the content protection features of this method and possible consequences that may ensue for violator of intellectual property and for the entity that directly created intellectual property